Spermatic cell characteristics in Gymnotiformes (Teleostei: Ostariophysi) and their phylogenetic meaning - Franca, G. F. [UNESP]; Oliveira, C. [UNESP]; Quagio-Grassiotto, I. [UNESP] (Wiley-Blackwell, 2009)
Spermatic characteristics were studied in representatives of the families Rhamphichthyidae, Sternopygidae and Apteronotidae, and compared with pre-existent data from Gymnotidae and Hypopomidae. The spermatic characteristics found in Gymnotiformes were also compared with data from other Ostariophysi spermatic cells. The spermatic characteristics as the type of spermiogenesis and the structural pattern of the sperm, considering nuclear form, pattern of chromatin condensation, nuclear fossa and its relation with the centriolar complex, form and localization of mitochondria, form of midpiece, presence or absence of cytoplasmic canal and cytoplasmic sleeve, and flagellar fins were utilized. The comparative analysis of the spermatic cell of Gymnotiformes better support the previous proposals for the order considering Gymnotidae as a derived group, than the more recent ones that located Gymnotidae in a basal position as the sister group of the remaining Gymnotiformes. Regarding the Ostariophysi, the comparative analyses based on the spermatic cell characteristics is consistent with a recent systematic proposal that consider Gymnotiformes as a sister group of Characiformes. (C) 2009 The Authors Journal compilation (C) 2009 The Fisheries Society of the British Isles
Keywords: evolution; freshwater fish; spermatozoa; spermiogenesis; systematic